High or Low? Writing the Irish Reformation in the Early Nineteenth Century. Issue 1 (1st April 2014) - Ford, Alan
Abstract: The Irish Reformation is a contentious issue, not just between Catholic and Protestant, but also within the Protestant churches, as competing Presbyterian and Anglican claims are made over the history of the Irish reformation. This chapter looks at the way in which James Seaton Reid (1798-1851), laid claim to the Reformation for Irish Dissent in his History of the Presbyterian Church in Ireland. It then examines the rival Anglican histories by two High Churchmen: Richard Mant (1775-1848), Bishop of Down and Connor; and Charles Elrington (1787-1850), the Regius Professor of Divinity in Trinity College, Dublin. It is clear that, in each case, theological and denominational conviction decisively shaped their history writing. Equally, however, significant advances were made by all three scholars in unearthing important new primary sources, and in identifying key points of controversy and debate which still represent a challenge to eccleciastical historians, of whatever denomination or none, today.